2008
DOI: 10.1021/jf801965n
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin and Hesperetin Induce Growth Arrest, Apoptosis, and Cytoplasmic Fat Deposit in Human Preadipocytes

Abstract: Citrus flavonoids are reported to be promising bioactive compounds against hyperlipidemia and lipid biosynthesis. However, the mechanism of the lipid lowering effect by flavonoids remains unknown. The present study examines the effect of some flavanones on the adipocytic conversion of the human preadipocyte cell line, AML-I. Among four structure-related flavanones including naringenin, naringenin-7-rhamnoglucoside (naringin), hesperetin, and hesperetin-7-rhamnoglucoside (hesperidin), the aglycones such as nari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
(50 reference statements)
5
17
3
Order By: Relevance
“…Naringin can accumulate in plasma after long-term intake, and they are distributed in tissues other than plasma [41]. Because of the limitation in detective analytical methods, distribution and accumulation of naringin in other tissues cannot be investigated [41,44]. Thus, we suggest that benefit health effects could ensue in individuals consuming orange or grapefruit products regularly if naringin actually has biological significances in vivo.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Naringin can accumulate in plasma after long-term intake, and they are distributed in tissues other than plasma [41]. Because of the limitation in detective analytical methods, distribution and accumulation of naringin in other tissues cannot be investigated [41,44]. Thus, we suggest that benefit health effects could ensue in individuals consuming orange or grapefruit products regularly if naringin actually has biological significances in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that naringin and naringenin (less than 50 mM) treatment had no effect on cell viability in several cell lines, although there were differences of the inhibition of cell proliferation between naringin and naringenin (more than 100 mM) treatment in different cell lines [41][42][43]. We used the concentration of naringin at 25 mM in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, apigenin can modulate Akt activity and trigger apoptosis in prostate cancer cells [4], naringenin and hesperetin alter fat metabolism and cause growth arrest [5] by mechanisms involving reactive oxygen species [6], the anthocyanin delphinidin causes apoptosis in PC3 cells [7], naringenin decreases the viability of colon cancer cells [8], hesperetin arrests the proliferation of vascular smooth muscle cells [9] and olive oil-derived phenolic compounds have a variety of reported effects on cells in culture [10,11]. Epigallocatechin gallate [1,[12][13][14] has been extensively studied and appears to have potential as an anti-cancer agent [1,15], rosmarinic acid promotes TNFa induced apoptosis [16], and resveratrol and curcumin have also attracted wide attention as possible health-maintaining and potential therapeutic agents [15,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%